PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 47 PEKANBARU - Rizawati, Fitria; Sahrilfuddin, Sahrilfuddin; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the value of lace IPS students, it is seen from the first half of the exam students are still under KKM, of the 22 students who achieve KKM only 6 students while students who do not reach the KKM is 16 students with an average value of 63.5, purpose of this research is to improve learning outcomes IPS grade IV with the implementation of cooperative learning index card game. This research is a classroom action research conducted in two cycles, each cycle includes planning, implementation, observation and reflection. Data were analyzed using analysis of the activities of teachers and students, the analysis of student learning outcomes, an average of learning outcomes and learning outcomes. Improve student learning outcomes can be seen from the average learning outcomes in basic scored 63.5 65.9 increase in the first cycle and the second cycle from a base score of 63.5 rose to 79.54. The results showed that the use of index cards learning model cooperative game proper in social studies learning, to improve learning outcomes IPS.Key words: cooperative model, index card match, learning, IPS